Sacrococcygeal Teratoma in Children- Experience in a Tertiary Military Hospital (Journal of Armed Forces Medical College, Bangladesh, 2017)
Introduction: Sacrococcygeal teratoma (SCT) is the most common solid tumour found in neonates. Most SCTs are reported in neonates and children, but SCTs are found in adults also. SCTs occur more commonly in females than males. If not detected antenatally, clinical features at birth are prominent in most cases as a palpable or visible mass. Surgery is the principal mode of treatment. The standard treatment for SCT with malignant elements is surgery and chemotherapy.Objective: To share the experience with sacrococcygeal teratoma, the most common tumour found in newborn in a tertiary military hospital.Materials and Methods: This observational study was carried out in the Department of Paediatric Surgery, CMH Dhaka during the period of January 2010 to December 2015. During the study period a total of 6 neonates with SCT were admitted in this hospital that were included in the study.Results: The age of the patients ranged from 3 days to 1 month. Out of them 5(83.33%) were female, 1(16.67%) was male with a female to male ratio of 5:1. Four neonates (66.67%) had type-I and 2(33.33%) had type II SCT. They were not diagnosed antenatally. All presented in neonatal period and were operated as elective cases. Five neonates (83.33%) were born by normal vaginal delivery and one (16.67%) was born by Caesarean section due to cervical dystocia. All patients had elevated alpha fetoprotein (AFP). Posterior sacral approach was sufficient in all the cases and histopathology revealed benign lesion. There was no perioperative death but 1 patient (16.67%) developed malignant recurrence within 1st year and 1 patient (16.67%) developed neurogenic bladder with bilateral hydronephrosis.Conclusion: SCTs are rare tumours that occur most frequently in neonates. Antenatal diagnosis is possible in many cases in this modern era. Follow up of cases after surgery should not only the look out for tumour recurrence, it includes the management of possible secondary urinary and/or bowel incontinence.Journal of Armed Forces Medical College Bangladesh Vol.13(1) 2017: 17-21